Financial Management Training As an Effort to Improve the Financial Performance of MSMEs at Pusat Glosir Cililitan (PGC) - Yusbardini Yusbardini (International Journal of Social Science and Community Service, 2024)
This community service project is titled "Financial Management Training as an Effort to Improve the Financial Performance of MSMEs Post-COVID-19 Pandemic." The general aim of this community service activity is to provide practical training and knowledge in financial management to enhance the financial performance of MSMEs in the future. The methods used include surveys and indirect (online) delivery of material, as well as discussions on financial management, techniques or strategies for improving financial performance, and the application of sound financial management practices. The conclusion of this community service project is that financial performance can be improved by maximizing the implementation of good financial management in daily activities, especially for MSMEs.